Grade 12 Student Career Needs and Perceptions of the Effectiveness of Career Development Services - Bloxom, Joan M.; Bernes, Kerry B.; Magnusson, Kris C.; Gunn, Thelma T.; Bardick, Angela D.; Orr, David T.; McKnight, Kerbi M. (Canadian Journal of Counselling and Psychotherapy, 2008)
High school students engaging in career decision making encounter signifi cant challenges due to changing social and economic conditions. The student needs assessment focus of this study provides unique insights into student perceptions of the effectiveness of high school career programs. Results indicated that Grade 12 students value resources that support transitions, have a passion for career, and report a wide range of occupational choices. However, students may not perceive career development resources available at the high school level as being very effective. Implications for the delivery of high school career programs and the development of public policy on career services are discussed.